Ideologi Pemberitaan LGBT Dalam Akun Instagram Pinterpolitik: Analisis Wacana Fairclough - Syahfitri, Iqssyzia; Khaerudin Kurniawan; Dadang S. Anshori (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This research was conducted by utilizing Norman Fairclough's concept of critical discourse. In this research, data collection method is done by collecting parts of texts which allegedly contain aspects of texts, discourses, and socio-cultural practices. In Indonesia society, LGBT is viewed as an illness which should not exist. However, there are still some parties who attempt to be a spokesman for LGBT group, for instance on Pinterpolitik Instagram account and Pinterpolitik website. So, this research aims to investigate how Pinterpolitik Online Media presents minority issues, particularly LGBT group, as the part of this media’s alignment towards LGBT equity, especially in the field of human rights and politics. The editor created an ideology through this report that minority inclusion, such as LGBTgroup, is not a key concern in Indonesia's cabinet. Then, the editor also stated that society should now be free of unfavorable attitudes against LGBT persons. Pinterpolitik is bold to express something against Indonesian beliefs and culture on equality in the context of Indonesian politics. Keywords: Critical Discourse, Online Media, LGBT, Pinterpolitik